Dinâmica populacional e ação de trichoderma no controle de fusariose em mudas de tomateiro e pepineiro - Ethur, Luciana Zago (2006)
Trichoderma spp. is at the present time, one of the fungi most studied as biocontrol agent, being antagonistic to several pathogens in different crops, besides promoting vegetable growth. The pathogen Fusarium oxysporum causes the fusarial wilt and is difficult to control mainly because of its capacity to remain in the soil for long periods, even without the presence of the host. Studies of the population dynamics of Trichoderma spp., Fusarium spp. and native microorganisms are necessary, mainly to observe the impact of the biocontrol agent addition to the soil. Vegetables as cucumber and tomato are commonly cultivated in South Brazil and are sensitive to a variety of diseases, as the fusarial wilt which is one of, their main diseases, specially in protected environment. For the biological control of the fusarial wilt in the cultivation of tomato and cucumber by Trichoderma and to study the population dynamics of the biocontrol agent when added to the soil, the following objectives were proposed: to study the space distribution of both Trichoderma and Fusarium in rhizosphere and bulk soil, in the cultivation of cucumber and tomato, in vegetable garden and greenhouse; to find a method for the mass selection of fungi isolates antagonistic to Fusarium solani and Fusarium oxysporum in microenvironment, and to identify the more effective ones; to verify the action of Trichoderma harzianum isolates in the development and protection of seedlings against the fusarial wilt of tomato and cucumer, identifying the best form of the biocontrol agent application in the control of the fusarial wilt; to analyze the population dynamics of Trichoderma and Fusarium, and of part of the microorganisms of the soil, with the addition of the biocontrol agents, in the cultivation of the tomato and cucumber, in greenhouse and vegetable garden. Both Trichoderma and Fusarium were found in the rhizosphere and bulk soil and the rhizosphere soil had the greater frequence of Trichoderma specially in greenhouse. The method of mass selection, in substrat, of fungi isolates antagonistic to the pathogens F. solani and F. oxysporum was efficient, since the three isolates of Trichoderma harzianum selected, besides reducing the population of the pathogens in substrate were also effective against the fusarial wilt of tomato and cucumber when applied as seed or substrate treatment. A population flutuation of Trichoderma spp. ocurred when isolates of T. harzianum were added to the soil in the cultivation of tomato and cucumber, in vegetable garden and greenhouse. There was a tendency of the population of Trichoderma spp. to return to the initial parameters, i.e. before the biocontrole agent was added to the soil. The population of bacteria, Fusarium spp. and general fungi did not show great alterations with the presence of the isolates of the biocontrol agent.